Two-year progress in experimental investigation on high-temperature superconductivity of sulfur hydride. (21st April 2017) - Einaga, Mari; Sakata, Masafumi; Masuda, Akiyoshi; Nakao, Harushige; Shimizu, Katsuya; Drozdov, Alexander; Eremets, Mikhail; Kawaguchi, Saori; Hirao, Naohisa; Ohishi, Yasuo
Abstract: The cooperation between theoretical and experimental investigations broke the record for the superconducting critical temperature T c in hydrogen sulfide at a high pressure at the end of 2014. Surprisingly, the material improved its highest T c by more than 30 K and showed conventional superconductivity, which can be explained by the Bardeen–Cooper–Schrieffer theory. Recent experimental works have gradually clarified the instability of the H2 S molecule and the pathway to the high- T c phase with a three-dimensional conductive structure unlike high- T c superconductors thus far. In this review, the present progress on a sulfur hydride system is reported.